An Inherent Multifunctional Sellotape Substrate for High‐Performance Flexible and Wearable Organic Single‐Crystal Nanowire Array‐Based Transistors. (4th July 2016) - Shang, Qixun; Deng, Wei; Zhang, Xiujuan; Wang, Liang; Huang, Liming; Jie, Jiansheng
Abstract : Sellotape, as a flexible, sticky, and lightweight substrate, can be integrated in electronic devices to realize unprecedented and low‐cost applications, such as biomedical devices, wearable electronics, smart clothes, and sensory skin for robotic system. However, very few works have successfully demonstrated fabricating devices on sellotape substrates, primarily because traditional microelectronic processing techniques, including photolithography, metallization, and lift‐off, are incompatible with sellotape. Here a novel tape‐stripping method is demonstrated for large‐area fabrication of high‐performance flexible and wearable organic nanowire array‐based field‐effect transistors (ONWFETs) on sellotape substrates. The copper phthalocyanine ONWFETs on the tapes exhibit high average mobility (≈1.02 cm 2 V −1 s −1 ) as well as high bending and wearing stability. Furthermore, 3D ONWFET circuitry consisting of five vertically stacked layers is demonstrated. Device geometries and electronic properties are maintained with high fidelity after sequential stacking processes. This is so far the first study of ONWFETs on flexible tapes and their applications in wearable or 3D integrated devices. It is anticipated that the novel tape stripping method may help overcome upcoming difficulties for organic flexible electronics. Abstract : A simple yet efficient sellotape stripping method is developed for achieving large‐area fabrication of high‐performance organic nanowire array‐based field‐effect transistors (ONWFETs) on flexible and wearable sellotape substrates. The ONWFETs exhibit several key features, including extreme high bending stability while being curved into a radius of 3 mm, fine wearing stability for multitimes wear, and ability to construct 3D multifunctional circuitry for up integration.